Tribalism and corruption : scale construction and explorations beyond natural culture - Abdelrahim, Yousif (University of Wisconsin--Whitewater, 2019)
The first essay in this dissertation develops and validates a new, reliable, scale for measuring and predicting individual tribal behavior within society using segmentary lineage theory (Evans-Pritchard, 1940). The primary measurement data were collected using a pencil-and-paper questionnaire survey. The newly developed tribalism scale suggested three reliable and valid dimensions for measuring tribalism at the individual level; these three dimensions are tribal pride, tribal loyalty, and tribal group identity. The second essay examines the relationships between tribalism and ethically suspect behaviors at the individual level; and tribalism and corruption at the country level. It further explores whether tribalism is a unique cultural behavior—different from Hofstede’s cultural dimensions and those of the GLOBE study. I used institutional anomie theory to develop my hypotheses relating tribalism to individuals’ ethically suspect behaviors. The present study used hierarchical linear modeling techniques (HLM) and multiple linear regression analysis of secondary datasets of 68,630 individuals from 56 countries. The secondary datasets were borrowed from the Jacobson and Deckard (2012) Tribalism Index (TI), the KOF Index of Globalization (KOFI), and the World Value Survey (WVS, sixth edition). The findings showed that tribalism is a unique cultural behavior that differs from Hofstede’s cultural dimensions (i.e., collectivism, masculinity, power distance, and uncertainty avoidance). I extended Hofstede’s cultural dimensions by identifying, validating, and showing the uniqueness of tribalism construct. Besides, the results confirmed that the concept of tribalism is positively related to corruption and that the relationship is weaker at a higher level of globalization. However, the results did not support the relationship between tribalism at the country level and ethically suspect behaviors at the individual level. Future research, theoretical and practical implications, and research limitations are also discussed.
This file was last viewed in Adobe Acrobat Pro.
Keywords: Tribes; Group identity; Corruption